EXPLORING MARKET OPPORTUNITIES: THE ROLE OF SEGMENTATION IN INCREASING SALES IN THE FOOD AND BEVERAGE INDUSTRY - Gunawan Gunawan (Sean Institute, 2022)
This study aims to understand the role of market segmentation in increasing sales of food and beverage products through a qualitative approach. In an increasingly competitive business environment, a deep understanding of consumer characteristics is key to designing effective marketing strategies. The research method used is qualitative with a descriptive approach, where data were collected through in-depth interviews with business actors in the food and beverage sector as well as direct observation of the marketing strategies implemented. The results show that market segmentation in the food and beverage industry is crucial for understanding differences in consumer tastes and needs. By segmenting the market based on demographics, taste preferences, lifestyle, and health aspects, companies can create more suitable products and effective marketing strategies. This approach helps improve consumer satisfaction and loyalty, opens opportunities for product innovation, and reaches new market segments, thus supporting sustainable business growth and company competitiveness.